A new DMSP magnetometer and auroral boundary data set and estimates of field‐aligned currents in dynamic auroral boundary coordinates. Issue 8 (10th August 2017) - Kilcommons, Liam M.; Redmon, Robert J.; Knipp, Delores J.
Abstract: We have developed a method for reprocessing the multidecadal, multispacecraft Defense Meteorological Satellite Program Special Sensor Magnetometer (DMSP SSM) data set and have applied it to 15 spacecraft years of data (DMSP Flight 16–18, 2010–2014). This Level‐2 data set improves on other available SSM data sets with recalculated spacecraft locations and magnetic perturbations, artifact signal removal, representations of the observations in geomagnetic coordinates, and in situ auroral boundaries. Spacecraft locations have been recalculated using ground‐tracking information. Magnetic perturbations (measured field minus modeled main field) are recomputed. The updated locations ensure the appropriate model field is used. We characterize and remove a slow‐varying signal in the magnetic field measurements. This signal is a combination of ring current and measurement artifacts. A final artifact remains after processing: step discontinuities in the baseline caused by activation/deactivation of spacecraft electronics. Using coincident data from the DMSP precipitating electrons and ions instrument (SSJ4/5), we detect the in situ auroral boundaries with an improvement to the Redmon et al. (2010) algorithm. We embed the location of the aurora and an accompanying figure of merit in the Level‐2 SSM data product. Finally, we demonstrate the potential of this new data set by estimating field‐aligned current (FAC) density using the Minimum Variance Analysis technique. The FAC estimates are then expressed in dynamic auroral boundary coordinates using the SSJ‐derived boundaries, demonstrating a dawn‐dusk asymmetry in average FAC location relative to the equatorward edge of the aurora. The new SSM data set is now available in several public repositories. Key Points: New DMSP magnetometer and auroral boundary data set Recomputed magnetic perturbations and calculated field‐aligned currents Estimated FAC density in dynamic auroral boundary coordinates shows dawn‐dusk asymmetry